Selective internal radiotherapy (SIRT) versus transarterial chemoembolization (TACE) for the treatment of intrahepatic cholangiocellular carcinoma (CCC): study protocol for a randomized controlled trial - Kloeckner, Roman (BioMed Central, 2014)
BACKGROUND: Cholangiocellular carcinoma is the second most common primary liver cancer after hepatocellular carcinoma. Over the last 30 years, the incidence of intrahepatic cholangiocellular carcinoma has risen continuously worldwide. Meanwhile, the intrahepatic cholangiocellular carcinoma has become more common than the extrahepatic growth type and currently accounts for 10-15% of all primary hepatic malignancies. Intrahepatic cholangiocellular carcinoma is typically diagnosed in advanced stages due to late clinical symptoms and an absence of classic risk factors. A late diagnosis precludes curative surgical resection. There is evidence that transarterial chemoembolization leads to better local tumor control and prolongs survival compared to systemic chemotherapy. New data indicates that selective internal radiotherapy, also referred to as radioembolization, provides promising results for treating intrahepatic cholangiocellular carcinoma. METHODS/DESIGN: This pilot study is a randomized, controlled, single center, phase II trial. Twenty-four patients with intrahepatic cholangiocellular carcinoma will be randomized in a 1:1 ratio to receive either chemoembolization or radioembolization. Randomization will be stratified according to tumor load. Progression-free survival is the primary endpoint; overall survival and time to progression are secondary endpoints. To evaluate treatment success, patients will receive contrast enhanced magnetic resonance imaging every 3 months. DISCUSSION: Currently, chemoembolization is routinely performed in many centers instead of systemic chemotherapy for treating intrahepatic cholangiocellular carcinoma confined to the liver. Recently, radioembolization has been increasingly applied to cholangiocellular carcinoma as second line therapy after TACE failure or even as an alternative first line therapy. Nonetheless, no randomized studies have compared radioembolization and chemoembolization. Considering all this background information, we recognized a strong need for a randomized controlled trial (RCT) to compare the two treatments. Therefore, the present protocol describes the design of a RCT that compares SIRT and TACE as the first line therapy for inoperable CCC confined to the liver. TRIAL REGISTRATION: ClinicalTrials.gov, Identifier: NCT01798147, registered 16(th) of February 2013.